A formação de professores e a (in)visibilidade da educação especial nos projetos pedagógicos dos cursos de licenciatura do Instituto Federal de Goiás - Souza, Calixto Júnior de (2017)
Based from the assumption that educational inclusion is a process and, in turn, the characteristic of being unfinished, it is necessary a constant analysis for the formation of teachers as a way, on the one hand, to remove its gaps and, on the other hand side, to seek the concretization of its advances in the face of the ephemerality of the social and educational relations of the contemporary world. The present study aimed to investigate the Pedagogical Projects of Courses (PPC) and the curricular matrices of the initial formation of teachers of the Federal Institute of Education, Science and Technology of Goiás (IFG) in order to analyze and discuss how the discipline in the undergraduate courses studied. In order to focus on the initial formation of teachers of the IFG, the specific objectives are to identify the presence of the discipline of Special Education and its contributions to the process of educational inclusion; understand how this institution makes it possible to include the students in a condition of disability through the documents analyzed; and, finally, to analyze how the PPC of the degree courses of the IFG are articulated with the process of educational inclusion, considering the curricular matrices as the “background” of this process. Therefore, a documental research with an exploratory study character skewed by a case study was adopted as methodological course, thus, it was based on the analysis of the PPC, curricular matrices, resolutions pertinent to the IFG as corpus that contribute to the articulation of the initial training of teachers of this institution. With regard to the PPC of IFG, 19 (nineteen) undergraduate courses were analyzed, and in only two campuses do they have the Special Education discipline as mediator of the knowledge related to the process of educational inclusion and, therefore, considering some elements disciplines, such as, for example, the disciplines that are taught and, also, the timetable of the disciplines. Despite the absence of a legal framework that contemplates the obligation of the Special Education discipline, given the data presented and analyzed, it is inferred the small number of courses that have this discipline as a constituent part of the curriculum, in order to address an allusion to the process of educational inclusion and certainly making a gap in the training of teachers for the construction of future teachers who seek to include pupils in a condition of deficiency in their pedagogical practices. As a result, it is becoming increasingly urgent to seek a critical and conscious teacher training in the process of educational inclusion with a view to building an educational foundation for quality education and, above all, an inclusive nature. Thus, in addition to the inclusion or exclusion of a discipline in the curriculum, it is necessary to rethink the articulation between knowledge and contents of the various disciplines so that a culture of interdisciplinarity can be created in undergraduate courses.